Sensitivity Analysis of North Surabaya Hospital Investment Feasibility - Lestyanto Wahyu; Andi Patriadi; Sajiyo Sajiyo (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
The aim of this research is to analyze the feasibility of investing in North Surabaya Hospital, Bulak District, Surabaya City with the parameters Net Present Value, Internal Rate of Return, Benefit Cost Ratio (BCR) and Payback Period. This research focuses on the North Surabaya Hospital which was built by the Surabaya City Government Health Service with a budget for 2026. The research instruments used were interview guidelines and observation sheets, with data collection procedures via location with related parties in the construction of the hospital, site observation, as well as documentation that includes primary and secondary data. Based on investment analysis of North Surabaya Hospital and evaluation of sensitivity to operational costs and potential income, the conclusion obtained is: Alternative 1 is feasible because it produces an NPV value of Rp. 211,014,227,005, IRR of 9.85%, BCR of 1.23 and PP of 7.69 years, but will be sensitive to the point that it is not feasible if there is an increase in hospital operational costs above 2.05% or a decrease in hospital service levy rates above 1.39% . Alternative 2 is not feasible because it produces an NPV value of Rp. 28,416,192,984, IRR of 6.57%, BCR of 1.14 and PP of 8.34 years, but it will be sensitive and feasible if there is a decrease in hospital operational costs above 7.73% or an increase in hospital service levy rates above 5.59%. Alternative 3 is not feasible because it produces an NPV value of Rp. 66,444,241,124, IRR of 7.30%, BCR of 1.16 and PP of 8.20 years, but it will be sensitive and feasible if there is a decrease in hospital operational costs above 5.7% or an increase in hospital service levy rates above 4.08%. Alternative 4 is feasible because it produces an NPV value of Rp. 166,294,504,181, IRR of 9.26%, BCR of 1.20 and PP of 7.70 years, but it will be sensitive to the point of being unfeasible if there is an increase in hospital operational costs above 0.15% or a decrease in hospital service levy rates above 0.10%.